The regional integration of commercial air transport in Africa : political, economic and legal considerations - Kaunda, Gideon H. (McGill University, 1983)
The introduction of this dissertation discusses geopolitical and socio-economic factors which influence transportation in Africa. Chapters II and III, respectively, analyse the concept of regionalism and the legal framework of multinational civil aviation co-operation. The economic advantages of surface and air transportation are compared in Chapter IV. Chapter V is a general survey of the impact of nationalism on socio-economic co-operation. To illustrate the extent of political problems, in economic and aeronautical co-operation, the former East African Community is reviewed in Chapter VI. The demised East African regional carrier is specifically discussed in Chapter VII. Chapter VIII highlights the notion in functionalism as an approach to the attainment of socio-economic integration. Multilateral organizations responsible for co-ordinating and fostering co-operation are examined in Chapters IX, X and XI. Current regional activities and future prospects are essessed in the penultimate chapter. The conclusion contains the essential elements required in creating regional airlines in Africa.
Keywords: Africa; Air transport; Commercial air transport; Regional integration

The 1975 Treaty of the Economic Community of West African States - ECOWAS Commission (1975)
Le traité de la Communauté économique des États de l’Afrique de l’Ouest (CEDEAO) est un accord multilatéral signé par les États membres qui formaient la Communauté économique des États de l’Afrique de l’Ouest. Le traité initial a été signé par les chefs d’État et de gouvernement des 16 États membres de l’époque en 1975 à Lagos, au Nigeria. Avec les nouveaux développements et mandats de la Communauté, un traité révisé a été signé à Cotonou, en République du Bénin, en juillet 1993 par les chefs d’État et de gouvernement des États membres actuels.